When Athlete Activism Clashes With Group Values: Social Identity Threat Management via Social Media. Issue 3 (3rd May 2016) - Sanderson, Jimmy; Frederick, Evan; Stocz, Mike
Abstract : On November 30, 2014, five African American St. Louis Rams players locked hands and displayed a "hands-up" gesture during player introductions in response to racial tensions in Ferguson, Missouri, emanating from the Michael Brown case. This act generated significant media attention and prompted discussions via Facebook and Twitter. Two notable venues on social media for these conversations were the "Boycott the St. Louis Rams" Facebook page and the Twitter hashtag #BoycottRams. A thematic analysis of 1, 019 user-generated Facebook comments and 452 tweets was conducted through the lens of social identity threat management. Six primary themes emerged: (a) renouncing fandom, (b) punishment commentary, (c) racial commentary, (d) general criticism, (e) attacking other group members, and (f) presenting the "facts" of the case. The results suggest that social media sites such as Facebook and Twitter serve as forums where group members discuss and debate challenges to group values and promote action steps that can mitigate social identity threats. This form of protest holds implications for minority athletes' activism efforts and sport organization administrators.